Healthy Social Media Practices in Preventing Body Dysmorphia Disorder: A Literature Review - Kembaren, Jordan Melias; Fahma, Hilmia (Journal of Diverse Medical Research: Medicosphere, 2025)
Background: Body Dysmorphic Disorder, also known as dysmorphia, is a psychiatric illness that can occur due to social media. This psychiatric illness causes a person to be very worried about their appearance, and often even think that their appearance is very bad. Objective: The purpose of this study is to describe a healthy way of social media to prevent Body Dysmorpich Disorder for its users.Methods: The method used is a literature review taken from several sources with a limit of 2019-2024. Results & Discussion: To prevent BDD, it is important to use social media in a healthy way. Steps that can be taken include limiting time on social media, following accounts that support body positivity, and engaging in real-world activities to boost self-confidence and distract from the pressures of social media. Conclusion: Healthy social media practices have been shown to prevent Body Dysmorphia Disorder in users.